Investigation of seat suspensions with embedded negative stiffness elements for isolating bus users’ whole-body vibrations - Papaioannou, Georgios; Sekulic, Dragan; Velenis, Efstathios; Antoniadis, Ioannis (Society of Automotive Engineers (SAE), 2021)
Bus drivers are a group at risk of often suffering from musculoskeletal problems, such as low-back pain, while bus passengers on the last-row seats experience accelerations of high values. In this paper, the contribution of K-seat in decreasing the above concern is investigated with a detailed simulation study. The K-seat model, a seat with a suspension that functions according to the KDamper concept, which combines a negative stiffness element with a passive one, is benchmarked against the conventional passive seat (PS) in terms of comfort when applied to different bus users’ seats. More specifically, it is tested in the driver’s and two different passengers’ seats, one from the rear overhang and one from the middle part. For the benchmark shake, both are optimized by applying excitations that correspond to real intercity bus floor responses when it drives over a real road profile. Then a human model is placed on the seats in order to compare their optimum solutions in terms of the user’s whole-body vibrations (WBVs), using objective comfort metrics. Based on the results, the K-seat improves significantly the comfort of the users (~92%) compared to the PS, while it achieves a similar decrease in the maximum values of the user’s back accelerations (~97%).
Keywords: Seats; Negative-stiffness; Low-back pain; Comfort; Wholebody vibrations; Bus users